2014
DOI: 10.1182/blood-2013-05-500876
|View full text |Cite
|
Sign up to set email alerts
|

Absence of STAT1 in donor-derived plasmacytoid dendritic cells results in increased STAT3 and attenuates murine GVHD

Abstract: Key Points • STAT12/2 BM prevents GVHD induced by delayed donor lymphocyte infusion via the expansion of CD92 Siglec H hi pDCs, which are low producers of IFNa and IL-12.• pDCs recovered from STAT1 2/2 BM chimeras show increased expression of S100A8, S100A9, and STAT3.Selective targeting of non-T cells, including antigen-presenting cells (APCs), is a potential strategy to prevent graft-versus-host-disease (GVHD) but to maintain graft-versus-tumor (GVT) effects. Because type I and II interferons signal through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…[20][21][22] Our data demonstrates that, at early time points and despite ongoing GVHD-induced immunesuppression, CAR T cells are still functional in generating a specific response toward their antigen, as evidenced by both in vitro assays of CAR T cells harvested post-adoptive transfer and in vivo clearance of leukemia. Despite this early preservation of allogeneic CAR T-cell functionality, the persistence of CAR T cells is significantly lower in the presence of acute GVHD than in syngeneic recipients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[20][21][22] Our data demonstrates that, at early time points and despite ongoing GVHD-induced immunesuppression, CAR T cells are still functional in generating a specific response toward their antigen, as evidenced by both in vitro assays of CAR T cells harvested post-adoptive transfer and in vivo clearance of leukemia. Despite this early preservation of allogeneic CAR T-cell functionality, the persistence of CAR T cells is significantly lower in the presence of acute GVHD than in syngeneic recipients.…”
Section: Discussionmentioning
confidence: 68%
“…on May 7, 2018. by guest www.bloodjournal.org From have diminished capacity to respond to vaccines and mediate antitumor responses even with mild subclinical GVHD, [20][21][22] and that adoptively transferred T cells with dual specificity for tumor and alloantigen through a single receptor demonstrate reduced but variable effectiveness dependent on the distribution of the allogeneic antigen. 23 Thus, we evaluated the efficacy of allogeneic CD19-targeted CAR T cells for the prevention of pre-B-cell ALL relapse in an immunocompetent murine model of HLA-matched, minor mismatched allo-BMT.…”
Section: Introductionmentioning
confidence: 99%
“…1 The safety advantage of reduced major bleeding was also consistent across the subgroups, except possibly in cancer patients, in whom the pooled estimate of a 23% RR reduction did not achieve statistical significance (supplemental data). 1 What are the implications for clinical practice? The DOACs should now replace vitamin K antagonists in most patients with VTE.…”
mentioning
confidence: 77%
“…Only 1 study before our series analyzed moDC after allogeneic HSCT, having observed higher NRM, and higher relapse rates in patients with lower moDC counts [16]. Previous studies have analyzed the association of DCs with the complex pathophysiology of GVHD with controversial results: some studies in mice have shown that pDC or mDCs may initiate aGVHD whereas others have shown that pDC may protect against aGVHD [33][34][35]. In the clinical setting, all series, including ours, showed that a low DC counts in the PB after transplantation are consistently associated with a higher incidence of aGVHD both in adults and in children [13,15,16,24,36].…”
Section: Discussionmentioning
confidence: 97%